Executive Functioning in Pediatric Solid Organ Transplant Recipients: A Meta-analytic Review. Issue 2 (February 2020) - Cushman, Grace K.; Stolz, Mary Gray; Blount, Ronald L.; Reed, Bonney
Abstract : Background: Examining executive functioning (EF) posttransplant has become increasingly prevalent, as EF deficits are associated with poor disease-related outcomes and psychosocial functioning. The purpose of the current meta-analysis was to compare overall and domain-specific EF between healthy youth and those with a kidney, heart, or liver transplant, and identify moderating variables related to EF differences between these 2 groups. Methods: A literature search of PsycINFO, Pubmed, and Medline was conducted for eligible articles published until January 2019. Twenty studies met eligibility criteria and were included in the present meta-analysis. Results: Results from the random-effects model indicated a significant standardized mean difference in overall EF skills with transplant recipients demonstrating worse EF ( g = 0.40; 95% confidence interval [CI], 0.29-0.50) than healthy youth. Specifically, transplanted youth had worse working memory ( g = 0.33; 95% CI, 0.01-0.66), processing speed ( g = 0.41; 95% CI, 0.19-0.62), attentional control ( g = 0.53; 95% CI, 0.33-0.73), and metacognitive skills ( g = 0.36; 95% CI, 0.18-0.54). Assessment type and time since transplantation were not significant moderators. Conclusions: Pediatric solid organ transplant recipients demonstrate worse overall EF skills and deficits in working memory, processing speed, attentional control, and metacognitive skills. Many children who have undergone solid organ transplantation will require additional support in medical and academic settings because of deficits in various EF domains.